NMR metabolomics as a complementary tool to brix-acid tests for navel orange quality control of long-term cold storage - Keeton H. Montgomery; Aya Elhabashy; Maria Del Carmen Reynoso Rivas; Gurreet Brar; V. V. Krishnan (Scientific Reports)
Abstract Quality control plays a crucial role in maintaining the reputation of agricultural organizations by ensuring that their products meet the expected standards and preventing any loss during the packaging process. A significant responsibility of quality control is conducting periodic product assessments. However, subjective interpretation during physical inspections of fruits can lead to variability in reporting. To counter this, assessing total soluble solids (Brix) and percent acidity (Acid) can provide a more objective approach. Nevertheless, it is essential to note that many fruit metabolites can impact these parameters. Nuclear magnetic resonance (NMR) spectroscopy, particularly 1H-NMR, has become a popular tool for quality control in recent years due to its precision, sample preservation, and high throughput analysis. This manuscript investigates if the standard Brix/Acid tests are directly related to the levels of metabolites during cold storage. Using citrus as the model system, a metabolomics analysis was conducted to identify patterns in the cold storage metabolite profiles of the juice, albedo, and flavedo tissues. The results show that Brix (or total dissolved solids) correlates well with sucrose, glucose, and fructose levels and moderately with choline levels. Acid (percent acidity) levels displayed a negative correlation with both fructose and choline levels. Interestingly, the formate levels were susceptible to storage time and directly related to Acid measurements. This study suggests metabolomics could be a complementary technique to quality control of fruits in cold storage, especially with cost-effective desktop NMR spectrometers.